Urinary proteomics in diagnosis of kidney diseases - Dutta, Pradip Kumar; Islam, Md Nazrul; Dutta, Arup (Journal of Chittagong Medical College Teachers' Association, 2011)
Keywords: proteomics; mass spectrometry; biomarkers DOI: http://dx.doi.org/10.3329/jcmcta.v22i1.9114 JCMCTA 2011; 22(1): 47-53